2013
DOI: 10.1073/pnas.1217308110
|View full text |Cite
|
Sign up to set email alerts
|

Inositol kinase and its product accelerate wound healing by modulating calcium levels, Rho GTPases, and F-actin assembly

Abstract: Wound healing is essential for survival. We took advantage of the Xenopus embryo, which exhibits remarkable capacities to repair wounds quickly and efficiently, to investigate the mechanisms responsible for wound healing. Previous work has shown that injury triggers a rapid calcium response, followed by the activation of Ras homolog (Rho) family guanosine triphosphatases (GTPases), which regulate the formation and contraction of an F-actin purse string around the wound margin. How these processes are coordinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
43
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 36 publications
7
43
0
Order By: Relevance
“…This could be due to the dependence on Ca 2+ dynamics for the proliferation of cell precursors of all regenerating tissues in the tail. Indeed, skin repair after wound healing in Xenopus embryos and skin homeostasis in human cells and mice depend on Ca 2+ stores for the enhancement of skin cell proliferation [37, 38]. Similarly, neural cell precursor proliferation is regulated by Ca 2+ dynamics [21, 35, 36].…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to the dependence on Ca 2+ dynamics for the proliferation of cell precursors of all regenerating tissues in the tail. Indeed, skin repair after wound healing in Xenopus embryos and skin homeostasis in human cells and mice depend on Ca 2+ stores for the enhancement of skin cell proliferation [37, 38]. Similarly, neural cell precursor proliferation is regulated by Ca 2+ dynamics [21, 35, 36].…”
Section: Discussionmentioning
confidence: 99%
“…TRH binding to a TRH GPCR isoform would trigger a signalling cascade involving phospholipase C, an increase in downstream inositol 1,4,5-trisphosphate (InsP 3 ) production and activation of protein kinase C. Intriguingly, a recent report using Xenopus embryonic wound healing assays has shown that both InsP 3 and its metabolite, inositol 1,3,4,5-tetrakisphosphate (InsP 4 ), are able to accelerate the speed of wound healing [72]. Further signalling events triggered by TRH binding can involve PKC-dependent or independent activation of mitogen-activated protein kinase (MAPK).…”
Section: Discussionmentioning
confidence: 99%
“…We developed an active Rho GTPase GST pull-down assay applicable to our in vivo embryonic wound-healing system, to detect the levels of active Rac, Rho and Cdc42 (supplementary material Fig. S7) (Soto et al, 2013). The binding domain of PAK1 (aa 70-117) was used for pulling down active Rac and Cdc42 (Zhang et al, 1998), and the binding domain of Rhotekin for active Rho (Benink and Bement, 2005).…”
Section: Erk and Pi3k Signalling Regulate Cytoskeleton Organisation Tmentioning
confidence: 99%